(untitled) (Superficies y Vacío, 2025)
Y2O3 gels co-doped with lanthanide ions (Ln3+) were synthesized based on the sol-gel process. Eu3+ was used in proportions of 2, 4, and 8 mol% and Tb3+ at a low and constant concentration of 0.075 mol% (Y2O3:Eu3+;Tb3+). The gels were subjected to supercritical drying (aerogel) at 73 bar and 34 °C and to thermal treatment at 800 °C to obtain crystalline materials (crystallized aerogels). Subsequently, each sample was sensitized in a novel way with 9 µmol of the compound 2-thenoyltrifluoroacetone (TTA) – Y2O3:Eu3+;Tb3+/TTA, to provide an antenna effect in order to focus the morphological, structural-chemical, and luminescent changes assigned to the energy transitions of Eu3+. When the crystal structure by X-ray diffraction (XRD) and the morphology by scanning electron microscopy (SEM) were analyzed, no drastic changes due to functionalization were observed. However, infrared (IR) and Raman spectroscopies were performed to identify the rare-earth oxides vibrational modes, although its main function was to reveal the adhesion of TTA to materials. The excitation-emission spectra were studied to evaluate the energy transfer to the Eu3+ activator ion and the influence of both the Tb3+ sensitizer and the TTA ligand on the luminescent properties of the samples Y2O3:Eu3+;Tb3+ and Y2O3:Eu3+;Tb3+/TTA, also the quantum yield corresponding to the highest luminescence samples was calculated. Based on the results, this class of materials can have novel and useful applications when TTA functionalization is fully exploited.